Non-agricultural labor from rural farmers in Bolivia: An analysis of determinants and effects - Lykke E. Andersen; Beatriz Muriel H.; Horacio Valencia (Institute for Advanced Development Studies (INESAD), 2009)
This paper analyses non-agricultural work supplied by rural households in Bolivia. It is shown that roughly 50% of all rural households complement their incomes through non-agricultural work, but that households in the lowlands are more likely to do so than households in the highlands. Since non-agricultural work pays several times better than agricultural work, access to this source of complementary income constitutes an important opportunity to escape rural poverty.
Keywords: J22; J43; R23; Q12; 330; Rural labor markets; Bolivia; non-farm labor